The Case for Advance Wave Causality - Lear, Charles (Journal of Scientific Exploration, 2019)
Abstract: We seek to strengthen the hypothesis of time reversal of cause and effect, or the bipolar causal nature of advanced and retarded waves. The hypothesis is not directly testable, at least with existing technology, so the argument is based on a priori reasoning. It provides a basis for rationalizing entanglement and for the Wheeler-Feynman absorber theory. Alternative hypotheses are given and compared to show justification. KeyWords: advance wave; retrocausation; causal time reversal; Occam’s razor; entanglement; Wheeler-Feynman absorber